Rhetorical Structure of Technical and Vocational Education and Training Video Lecture Introductions - Shamsudin, Sarimah; Izzat Rahim, Muhamad (Opción)
Considering the importance of rhetorical structure in listening to lectures, this study aims to investigate the rhetorical structure of Technical and Vocational Education and Training (TVET) video lecture introductions. Five video lectures by Malaysian Polytechnics were analyzed using the ESP genre approach. The results show that TVET video lecture introduction commonly consists of two moves and three steps. Additionally, it was found that the rhetorical structure for introduction differs from one video lecture style to another. In conclusion, TVET students can utilize the rhetorical structure of TVET video lecture introductions as a mental map in listening to video lectures